Pursuing competitiveness: A comparative study of commercial beekeepers - Duarte Alonso, Abel; Kok, Seng; O'Shea, Michelle; Koresis, Alex (Taylor & Francis, 2020)
This empirical study examines how commercial beekeepers operating in the New Zealand and the United Kingdom are working to improve their firms’ competitiveness, namely, through innovating and adding value to their honey production, and what they perceive to be the strengths, weaknesses, opportunities and threats (SWOT) within the context of their business. An online questionnaire was employed to gather data from beekeepers operating in the United Kingdom and New Zealand. While both groups perceived innovation in similar ways, they differed regarding equipment and infrastructure development, with New Zealand beekeepers more strategically involved in this area. Similarly, both commonalities and significant differences were revealed concerning adding value, and regarding aspects related to the SWOT framework. These findings have important implications, for instance, in highlighting the importance of identifying strategies that, regardless of beekeepers’ geographical context, can help improve the competitiveness of their operations and their industry.